The Use of Imperative Verbs in Radio Advertising Texts - Mukhammadovna, Jurayeva Maksuda; Matluba, Abdurahmanova (Journal of Innovation in Education and Social Research, 2025)
This article examines the use of imperative verbs in French radio advertising texts. Imperative verbs, as an important element of advertising communication, are widely used to motivate listeners to take active action and encourage them to perform a certain behavior. The article analyzes the syntactic and semantic properties of imperative verbs, as well as their role and effect in advertising texts. Using examples of French advertising, it shows how imperative verbs are used in different contexts. It also discusses the impact of imperative verbs on the audience, their importance in attracting their attention and increasing interest in the brand. The article also provides recommendations aimed at increasing the effectiveness of advertising by studying the positive and negative aspects of imperative verbs, their cultural context, and the psychological reactions of listeners.